Hypnoanalgesia and the study of pain experience: from Cajal to modern neuroscience - Lanfranco, Renzo C.; Canales-Johnson, Andrés; Huepe, David (Frontiers in Psychology, 2014)
Santiago Ramón y Cajal (1852-1934) did not only contribute to neurobiology and neurohistology. At the end of the 19th century, he published one of the first clinical reports on the employment of hypnotic suggestion to induce analgesia (hypnoanalgesia) in order to relieve pain in childbirth. Today, the clinical application of hypnoanalgesia is considered an effective technique for the treatment of pain in medicine, dentistry and psychology. However, the knowledge we have today on the neural and cognitive underpinnings of hypnotic suggestion has increased dramatically since Cajal’s times. Here we review the main contributions of Cajal to hypnoanalgesia and the current knowledge we have about hypnoanalgesia from neural and cognitive perspectives.